A review of adverse events linked to dopamine agonists in the treatment of Parkinson's disease. Issue 2 (1st February 2016) - Ceravolo, Roberto; Rossi, Carlo; Del Prete, Eleonora; Bonuccelli, Ubaldo
ABSTRACT: Introduction : Dopamine agonists are highly effective as adjunctive therapy to levodopa in advanced Parkinson's disease. These drugs have rapidly gained popularity as a monotherapy in the early stages of Parkinson's disease for patients less than 65–70 years old since they are about as effective as levodopa but patients demonstrate a lower tendency to develop motor complications. However, dopamine agonists could have peripheral and central side-effects which are often the reason for the discontinuation of the treatment. Areas covered : This article presents an overview of the efficacy and the potential negative effects related to the use of dopamine agonists in the treatment of Parkinson's disease. Expert opinion : Beyond the new generation non ergot dopamine agonists, no strong evidences allow the choice of a specific dopamine agonists for Parkinson 's disease treatment and by now dopamine agonists treatment should be tailored on specific adverse events profile.